2005
DOI: 10.1111/j.1471-4159.2005.03224.x
|View full text |Cite
|
Sign up to set email alerts
|

Dicer and eIF2c are enriched at postsynaptic densities in adult mouse brain and are modified by neuronal activity in a calpain‐dependent manner

Abstract: We have hypothesized that small RNAs may participate in learning and memory mechanisms. Because dendritic spines are important in synaptic plasticity and learning, we asked whether dicer, the rate-limiting enzyme in the formation of small RNAs, is enriched within dendritic spines. In adult mouse brain, dicer and the RNA-induced silencing complex (RISC) component eIF2c were expressed in the somatodendritic compartment of principal neurons and some interneurons in many regions, and dicer was enriched in dendriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
248
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(270 citation statements)
references
References 46 publications
20
248
0
2
Order By: Relevance
“…The experiments blocking these homeostatic changes with the miR-I support this conclusion. Mature miR-485 levels were elevated by increased excitatory activity in hippocampal neurons, and other studies show that the miRNA processing enzyme Dicer is regulated in a Ca 2+ -dependent manner (35), suggesting that pre-miRNAs targeted to synapses may undergo processing into mature miRNAs in an activity-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…The experiments blocking these homeostatic changes with the miR-I support this conclusion. Mature miR-485 levels were elevated by increased excitatory activity in hippocampal neurons, and other studies show that the miRNA processing enzyme Dicer is regulated in a Ca 2+ -dependent manner (35), suggesting that pre-miRNAs targeted to synapses may undergo processing into mature miRNAs in an activity-dependent manner.…”
Section: Discussionmentioning
confidence: 98%
“…Although it remains to be determined whether they interact in primary leukocytes, the relatively weak coimmunoprecipitation between 5LO and Dicer proteins suggests that this Dicer 5LObd-mediated interaction may be transient, conditional and/or require structural changes in Dicer conformation. Whether Dicer 5LObd becomes exposed to the surface (i) of an alternatively spliced variant form of Dicer, (ii) following protease-directed cleavage, as observed in the case of calpain-mediated release of Dicer fragments [38], (iii) in association with an enhanced enzyme activity induced by limited proteolysis [3], or (iv) upon covalent modification, such as phosphorylation, also remains to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…Initially, it was found that Dicer is activated in response to activity by limited proteolysis due to cleavage by the calcium-dependent protease calpain. This resulted in increased RNAse III activity of Dicer on dsRNA substrates [29]. In a more recent study, BDNF-mediated stimulation of the ERK pathway was shown to stabilize Dicer protein levels via phosphorylation of TRBP [30].…”
Section: Regulation Of Mirnas By Neuronal Activity (A) Activity-depenmentioning
confidence: 99%